2021
DOI: 10.1002/jcb.29892
|View full text |Cite
|
Sign up to set email alerts
|

Calmodulin/CaMKII‐γ mediates prosurvival capability in apicidin‐persistent hepatocellular carcinoma cells via ERK1/2/CREB/c‐fos signaling pathway

Abstract: Calmodulin (CaM), a Ca2+ binding protein, plays a critical role in cancer initiation and progression through binding and activating numerous target proteins, including Ca2+/calmodulin‐dependent protein kinase (CaMK) family proteins. However, the mechanisms underlying the effects of CaM/CaMKs on the survival capability of liver cancer cells is unclear, and this study investigates this mechanism in apicidin‐persistent HA22T cells. CaM level was upregulated, especially in the cytosol, in apicidin‐persistent HA22T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 48 publications
0
11
0
Order By: Relevance
“…Previous studies have shown that calcium calmodulin dependent kinases (CAMK1 and CAMK2) phosphorylate and activate the transcription factor (Cyclic AMP Response element binding protein) CREB at Ser133 in vitro. However, this has never been shown for PNCK [23][24][25][26]. We observed that PNCK overexpression led to increased pCREB signal, as measured by immunofluorescence (Figure 2C, F, I, L)).…”
Section: Pnck Overexpression Leads Tomentioning
confidence: 64%
“…Previous studies have shown that calcium calmodulin dependent kinases (CAMK1 and CAMK2) phosphorylate and activate the transcription factor (Cyclic AMP Response element binding protein) CREB at Ser133 in vitro. However, this has never been shown for PNCK [23][24][25][26]. We observed that PNCK overexpression led to increased pCREB signal, as measured by immunofluorescence (Figure 2C, F, I, L)).…”
Section: Pnck Overexpression Leads Tomentioning
confidence: 64%
“…CAMKK1 encodes calcium/calmodulin dependent protein kinase kinase 1 that activates calcium/calmodulin dependent protein kinase (CAMK). CAMK plays a central role in calcium/calmodulin-dependent signaling cascades implicated in cell survival and carcinogenesis ( 20 ). The genes associated with the metabolic process of small molecules which were downregulated include CYP26C1 and SLC26A1 in AGS and ACSL6 and PNLIPRP2 in SW948 cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…activation [32]. These findings suggest that CaMKII-CREB is linked with differentiation, proliferation, apoptosis, and tumorigenicity; however, its role in the regulation of CRT remains unclear.…”
Section: Introductionmentioning
confidence: 92%
“…Additionally, the CaMKII is a cancer marker that is frequently overexpressed and regulates cell proliferation, survival, invasion, and migration in various cancer types [ 31 ]. Our previous study demonstrated critical roles of CaM/CaMKII-γ pathway in the apicidin-persistent HCC prosurvival capability via ERK1/2/CREB/c-fos signaling activation [ 32 ]. These findings suggest that CaMKII-CREB is linked with differentiation, proliferation, apoptosis, and tumorigenicity; however, its role in the regulation of CRT remains unclear.…”
Section: Introductionmentioning
confidence: 99%